Variation of Secondary Metabolite Contents and Activities against Bovine Diarrheal Pathogens among Zygophyllaceae Species in Benin and Implications for Conservation - Ouachinou, Jéronime Marie-Ange Sènami; Dassou, Gbèwonmèdéa Hospice; Agbankpé, Alidehou Jerrold; Koudoro, Yaya Alain; Agbangnan, Pascal; Hidalgo Triana, Noelia; Favi, Gnimansou Abraham; Djidohokpin, Donald; Adomou, Aristide Cossi (Planta Medica, 2022)
Balanites aegyptiaca is a wild plant species largely used in folk medicine and a priority fruit tree in West Africa. In Benin, its overexploitation for ethnoveterinary uses could lead to its rarity or extinction in the long term. In this study, we evaluate the possibilities of its substitution by other Zygophyllaceae species. This study was based on optimal defense theory, which distinguished 2 categories of plants: K-strategist species and r-strategist species. Phytochemical screening was carried out based on aqueous extracts of the leafy stems of B. aegyptiaca and Guaiacum officinale (K-strategist species) and Tribulus terrestris and Kallstroemia pubescens (r-strategist species) for the identification of chemical compounds. The phenolic compounds were quantified by quercetin and vanillin methods. The extracts were tested against 5 bacterial strains responsible for severe diarrhea in bovines. Our results indicated the presence of many phytochemicals, such as alkaloids, flavonoids, saponosides, and tannins. The diversity in secondary metabolites is higher for r-strategist than K-strategist species. The contents of total polyphenols ranged from 4.82 ± 0.05 to 41.84 mg GAE/g of extract. The flavonoid contents varied from 30.64 ± 0.35 to 57.11 ± 0.13 mg QE/g of extract and those of the tannins from 0.04 ± 0.00 to 0.06 ± 0.01 mg PE/mL. The sensitivity of the bacterial strains showed a significant dependence on the extracts. Of the species, K. pubescens showed a bactericidal activity on the majority of strains tested and thus could be a potential substitute for B. aegyptiaca in the treatment of infectious diarrhea.
Keywords: substitution; Balanites aegyptiaca; Zygophyllaceae; ethnoveterinary uses; antibacterial activity; West Africa